Recent Advances in Strategies for Improving the Performance of CO2 Reduction Reaction on Single Atom Catalysts - Wang, Qiyou; Cai, Chao; Dai, Minyang; Fu, Junwei; Zhang, Xiaodong; Li, Huangjingwei; Zhang, Hang; Chen, Kejun; Lin, Yiyang; Li, Hongmei; Hu, Junhua; Miyauchi, Masahiro; et al. (Small Science, 2021)
Excessive consumption of fossil fuels gives rise to the increasing emission of carbon dioxide (CO2) in the atmosphere and furthers the ecocrisis. Electrochemical CO2 reduction (ECR) has both functions of dwindling greenhouse gas concentration and converting it into valuable products. Due to the intrinsic chemical inertness of CO2 molecules, the study on efficient and low‐cost catalysts has attracted much attention. Recently isolated atoms, dispersed in stable support, play an important role in decreasing energy barriers of intermediate steps and obtaining target products with high activity and selectivity for ECR. The effective regulation of central atoms or coordination environment is significant to realize the desired performances of ECR with a high efficiency and selectivity. Hence, a comprehensive summary about strategies for improving the performance of ECR on single atom catalysts (SACs) is necessary. Herein, the SACs on various supports are introduced, the methods to design stable SACs are discussed, and the strategies for tuning the performance of ECR on SACs are summarized. The localized environment manipulation is widely used for high‐performance SACs design, including regulating central atoms and coordination environment. Finally, the perspectives are discussed to shed light on the rational design of intriguing SACs for ECR. The performance of single atom catalysts (SACs) in carbon dioxide (CO2) electroreduction is closely related to the central atoms and its coordination environment. Strategies which include regulating the central atoms, coordination atoms, coordination number, and diatomic strategies are successfully developed to enhance the performance of SACs in CO2 reduction reaction.